Organizational Change and Employee Performance in Higher Education Institutions in Nepal - Prajapati, Mamata (International Research Journal of MMC, 2026)
In modern institutions, organizational change is a crucial phenomenon that influences both employee performance and the overall efficiency of the institution. This study looks at how employee performance in Nepal’s reaccredited higher education institutions (HEIs) is affected by organizational change, particularly changes in leadership and technology. A standard self-reported questionnaire was used to gather data from 270 employees of 11 reaccredited HEIs using a quantitative research approach. Multiple regression analysis and exploratory factor analysis were used in the study to evaluate the correlations between the variables. The results show that while leadership change has no statistically significant impact on employee performance, technology change considerably improves it. Employee performance and technology change were found to be strongly positively correlated by correlation analysis. Nonetheless, the weak association between leadership and technology advancements implies that these elements function separately. These results highlight the critical role that technology plays in increasing worker productivity and the necessity of making calculated investments in digital infrastructure and staff development. On the other hand, leadership changes by themselves could not have a direct impact on performance results, hence more research into the contextual elements affecting leadership efficacy is required. In addition to offering empirical insights for HEI administrators and policymakers to use in developing evidence-based methods to improve employee performance in the face of institutional upheavals, this study adds to the theoretical conversation on organizational change.